Regulation of the V-type ATPase by redox modulation - Seidel, Thorsten; Scholl, Stefan; Krebs, Melanie; Rienmüller, Florian Christian; Marten, Irene; Hedrich, Rainer Franz; Hanitzsch, Miriam; Janetzki, Patricia; Dietz, Karl-Josef; Schumacher, Karin (Biochemical journal, 2012)
ATP-hydrolysis and proton pumping by the V-ATPase (vacuolar proton-translocating ATPase) are subject to redox regulation in mammals, yeast and plants. Oxidative inhibition of the V-ATPase is ascribed to disulfide-bond formation between conserved cysteine residues at the catalytic site of subunit A. Subunits containing amino acid substitutions of one of three conserved cysteine residues of VHA-A were expressed in a vha-A null mutant background in Arabidopsis. In vitro activity measurements revealed a complete absence of oxidative inhibition in the transgenic line expressing VHA-A C256S, confirming that Cys256 is necessary for redox regulation. In contrast, oxidative inhibition was unaffected in plants expressing VHA-A C279S and VHA-A C535S, indicating that disulfide bridges involving these cysteine residues are not essential for oxidative inhibition. In vivo data suggest that oxidative inhibition might not represent a general regulatory mechanism in plants.